2008
DOI: 10.1080/13691050701564678
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the internet's role in sexual compulsivity and out of control sexual thoughts/behaviour: A qualitative study of gay and bisexual men in New York City

Abstract: Sexual compulsivity and the internet have been investigated separately among gay and bisexual men for their connection to sexual risk behaviour, yet little research has addressed the intersection. This analysis explored qualitative interview data from 111 gay and bisexual men experiencing out of control sexual thoughts and/or behaviours, about the role of the internet in their lives. For some it facilitated their problematic sexual thoughts and behaviours and, to some extent, was a distraction from important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 45 publications
4
29
0
5
Order By: Relevance
“…The symptoms relevant for a diagnosis of addiction experienced by this sample included preoccupations with sexual thoughts and behaviours, strong urges for sex, loss of control, the use of sex as coping mechanism, negative consequences, and a significant loss of time (Grov, Bamonte, Fuentes, Parsons, Bimbi, & Morgenstern, 2008). Overall, the results of this study emphasized the pathological nature of sex addiction.…”
Section: Internet Sex Addiction In Adults: Empirical Qualitative Studiesmentioning
confidence: 64%
See 1 more Smart Citation
“…The symptoms relevant for a diagnosis of addiction experienced by this sample included preoccupations with sexual thoughts and behaviours, strong urges for sex, loss of control, the use of sex as coping mechanism, negative consequences, and a significant loss of time (Grov, Bamonte, Fuentes, Parsons, Bimbi, & Morgenstern, 2008). Overall, the results of this study emphasized the pathological nature of sex addiction.…”
Section: Internet Sex Addiction In Adults: Empirical Qualitative Studiesmentioning
confidence: 64%
“…Here again, the presence of depressive symptoms may account for the pathological status of Internet sex addiction. Grov, Bamonte, Fuentes, et al, (2008) explored the Internet's role in sexual compulsivity by means of conducting qualitative interviews with a sample of 111 homosexual and bisexual men who experienced sexual behaviours and thoughts that were out of control. These men were recruited using a targeted sampling framework (Watters & Biernacki, 1989).…”
Section: Internet Sex Addiction In Adults: Empirical Qualitative Studiesmentioning
confidence: 99%
“…In that review, only 14 empirical studies of Internet sex addiction in adults were identified that met all of the inclusion criteria (nine quantitative studies [29][30][31][32][33][34][35][36][37] and five qualitative studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41]). …”
Section: Empirical Research Into Online Sex Addictionmentioning
confidence: 99%
“…According to Bancroft (2008) and Grov et al (2008), there are some gay and bisexual men who are experiencing sexual thoughts/behaviors perceived as "out of control." Thus, the use of the Internet to seek sexual partners may be associated with, in some cases, compulsive behaviors (Engler, Frigault, Léobon, & Lévy, 2007;Kalichman, Cherry, Cain, Pope, & Kalichman, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Men interested in finding sex on the Internet now have a powerful communication tool that is comfortable (e.g., it can be used from home), anonymous, acceptable (the norm in the gay community, given its acceptance by mostly gay men), cheap, and very widely available (Grov et al, 2008).…”
mentioning
confidence: 99%